EVALUATION OF INDICATIONS FOR CESAREAN SECTION AND PERINATAL OUTCOMES IN TWIN PREGNANCIES FROM 23 WEEKS AT THAI BINH OBSTETRICS AND GYNECOLOGY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze the indications for cesarean section and perinatal outcomes in twin pregnancies from 23 weeks at Thai Binh Obstetrics and Gynecology Hospital.Subjects and methods: A cross-sectional descriptive study was conducted on 133 pregnant women carrying twins from September 2024 to June 2025. Data were analyzed using multiple logistic regression (SPSS 27.0).Results: The incidence of cesarean section was 84.2%, mainly due to unfavorable fetal presentation (63.9%) and maternal pathology (55.6%). Regression analysis confirmed that maternal systemic pathology (p < 0.001) and gestational age (p = 0.003) were independent prognostic factors for cesarean section indication. The mean birth weight ranged from 2230 to 2237 gram. Despite high NICU admission rates (42.1-48.1%), over 90% of infants achieved good 5-minute Apgar scores (≥ 8 points). The referral rate remained low (≤ 6%).Conclusion: The decision to perform multiple births in twin pregnancies is heavily influenced by maternal health and gestational age. The favorable perinatal outcome demonstrates the effectiveness of local obstetric-pediatric collaboration.
Keywords: Twin pregnancy, cesarean section, perinatal outcomes, logistic regression.